2013
DOI: 10.5056/jnm.2013.19.3.381
|View full text |Cite
|
Sign up to set email alerts
|

Regional Differences in Hospitalizations and Cholecystectomies for Biliary Dyskinesia

Abstract: Background/AimsPublished studies suggest that socioeconomic factors contribute to increasing cholecystectomy rates for biliary dyskinesia (BD). The aim of this study was to identify factors driving admissions and operations for BD by examining regional variability in hospitalizations and cholecystectomies for this disorder.MethodsAnnual hospitalizations and cholecystectomy rates for biliary diseases were assessed using the State Inpatient Databases of the Agency for Healthcare Research and Quality based on dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Similarly, an increased rate in GBD over time also was detected in the Mayo Clinic clinical data, although growing at a slower rate than previously described 12 . Marked regional variations appear to exist in the diagnosis of GBD, with a higher proportion of patients in the central and southern states 13 . In a cross-sectional survey of adults with functional gastrointestinal disorders only 0.2% met the Rome IV criteria for functional GB pain 14 .…”
Section: Incidencesupporting
confidence: 56%
See 1 more Smart Citation
“…Similarly, an increased rate in GBD over time also was detected in the Mayo Clinic clinical data, although growing at a slower rate than previously described 12 . Marked regional variations appear to exist in the diagnosis of GBD, with a higher proportion of patients in the central and southern states 13 . In a cross-sectional survey of adults with functional gastrointestinal disorders only 0.2% met the Rome IV criteria for functional GB pain 14 .…”
Section: Incidencesupporting
confidence: 56%
“…12 Marked regional variations appear to exist in the diagnosis of GBD, with a higher proportion of patients in the central and southern states. 13 In a cross-sectional survey of adults with functional gastrointestinal disorders only 0.2% met the Rome IV criteria for functional GB pain. 14 Interestingly, the diagnosis of GBD is much lower in other countries.…”
Section: Incidencementioning
confidence: 99%
“…The incidence of FGBD in Olmsted County (1.8/10.000) was much lower than the previously published incidence in administrative data for Minnesota (30/10,000). 11 Only a small fraction of patients (11%) with the ICD-9 code 575.8 for unspecified gallbladder diagnosis had FGBD compared to the State Inpatient Sample which reported that FGBD accounted for more than 80% of administrative code 575.8. It is unclear if that is a single studies overestimation/practice pattern that has informed a number of large scale data reviews or if this difference is specific to the Rochester Epidemiology Project.…”
Section: Discussionmentioning
confidence: 95%
“…7 In the absence of any truly definitive studies, there has been a growing discrepancy between expert consensus and the common practice of cholecystectomy in the absence of stone disease with several authors calling for RCTs. 811…”
Section: Discussionmentioning
confidence: 99%